Recognising the newcomer: education policy and teaching practices in Norway and England - Soye, Emma; Hilden, Per Kristian; Andersen, Arnfinn; Watters, Charles (Frontiers in Education, 2024)
Education policies in different countries recognise the needs and abilities of newcomer students in different ways, with consequences for their social inclusion and academic progress at school. We highlight the importance of context to debates around the politics of recognition in newcomer education by drawing on qualitative research in Norwegian and English secondary schools. Taylor's (1994) political theory of 'recognition' provides the analytical lens through which we explore how teachers perceive newcomer students to be recognised (or not) in national education policies in each country. We underscore teachers' agency in responding to these policies through their own politics of recognition at school.